Göltepe excavations : tin production at an early Bronze Age mining town in the central Taurus Mountains, Turkey - Yener, K. Aslihan (Prehistory monographs, 2021)
"This volume presents over fifteen years (1981-1996) of archaeometallurgy surveys and specifically the excavations of an Early Bronze Age miners' village, Göltepe, and its associated tin mine, Kestel. The results of the surface surveys, test pit operations, profile trenches and excavation finds demonstrate that processing of cassiterite-rich ore was the primary function of activities at Göltepe. The variety and density of tin-rich vitrified crucibles as well as ground, powdered tin-rich ore from excavated contexts were only some of the several lines of evidence. Other finds indicated that the site was profoundly associated with metal production. Weighty evidence came in the numbers of multifaceted molds, ingots and tin bronze artifacts. Furthermore, 50,000 ground stone tools for ore dressing and vitrified material grinding were estimated on the site surface, while 5,000 came from excavated contexts. Early Bronze Age Göltepe and Kestel Mine represent the as-yet unique example of the highland production model, that is, the industrial tier 1 of the extraction and processing of raw materials for the production of metal artifacts. This model entails the mining and smelting operations in the metalliferously rich ore deposits and forests, usually located in the mountains, in this case, the central Taurus Mountains in southern Turkey"--